2016
DOI: 10.1021/acs.jpcc.6b09248
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical, Electronic, and Optical Properties of Mg-Doped AlGaN

Abstract: Hydrogen, carbon, and oxygen are common unintentional impurities of Al (x) Ga (1−x) N crystals. This impurity structure and its interplay with Mg impurities in Al (x) Ga (1−x) N semiconductors are relevant to develop the p-type nitride crystals for various devices (e.g, LEDs, transistors, gas sensors) but are still unclear. Here we have investigated Mg-doped Al 0.5 Ga 0.5 N before and after postgrowth annealing with valence-band and core-level photoelectron spectroscopy, photoluminescence, and resistivity meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…58,59 Moreover, the oxygen atoms opt to incorporate into AlGaN rather than GaN because of the high reactivity of Al. 60,61 By introducing the Mg dopants at a low temperature (280°C), the net ionized dopant density decreased due to the partial compensation of the unintentional n-type conductivity. 39 As the temperature reached 360°C, the net ionized dopant concentration was 1.3 × 10 19 cm −3 due to the increase in the number of thermally ionized acceptors, which corresponds to the free hole density at RT.…”
Section: Resultsmentioning
confidence: 99%
“…58,59 Moreover, the oxygen atoms opt to incorporate into AlGaN rather than GaN because of the high reactivity of Al. 60,61 By introducing the Mg dopants at a low temperature (280°C), the net ionized dopant density decreased due to the partial compensation of the unintentional n-type conductivity. 39 As the temperature reached 360°C, the net ionized dopant concentration was 1.3 × 10 19 cm −3 due to the increase in the number of thermally ionized acceptors, which corresponds to the free hole density at RT.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the appearance of a new species along with Mg coordination into tri- s -triazine. After fitting treatment, an extra N–Mg signal at 400.04 eV has been confirmed in Mg- s -triazine apart from the common pyridinic and graphitic N in tri- s -triazine (top image in Figure h). Mg coordination within tri- s -triazine is then further examined using near-edge X-ray absorption fine structure (NEXAFS) spectroscopy as shown in Figure i.…”
Section: Resultsmentioning
confidence: 98%
“…20 Though no typical signal for Mg-containing groups was detected in XRD, FT-IR, or SSNMR spectra of Mg-striazine due to the low content of Mg, an ∼1 ppm chemical shift in the 15 N SSNMR spectra indicates the possible interaction of Mg with pyridinic N in tri-s-triazine (Figure S2b,c). Subsequently, in the Mg 2p fine spectra of XPS (Figure 1g), the only main symmetrical signal at 50.8 eV for Mg-s- triazine samples is identified as the Mg−N binding state, 21,22 which is much similar to that for chlorophyll. While for Mg-striazine-3, the half-peak width broadens slightly to a highenergy position, meaning a tiny amount of the Mg oxide species has been generated, which is consistent with HAADF-STEM observations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This result is consistent with the report of R. Armitage [ 14 ], in which the blue band is observed in undoped semi-insulating GaN and intentionally C-doped GaN and BL band are attributed to carbon. Meanwhile, J. Mäkelä et al reported the presence of deep states up to 1 eV above the valence-band maximum and the model of C N -related blue emission photoluminescence in Mg-doped Al 0.5 Ga 0.5 N [ 21 ]. In fact, the origin of the BL band of GaN is still in dispute.…”
Section: Resultsmentioning
confidence: 99%